(untitled) (Journal of Nepal Geological Society, 2018)
Groundwater is the water which is present in pore spaces and in the fractures of the geological materials beneath earth surface. Water is incompressible substance and presence of small amount of water in geological material modifies the behavior of geological material under stresses. Determination of engineering behavior of the geological material is almost impossible skipping the role of water. The objective of this study was to map and evaluate shallow groundwater level of the northern Kathmandu Valley covering main rivers such as the Bagmati River, Bishnumati River, Dhobi Khola and the Manahara Khola. These rivers flow from the North to the South across the sand rich sediment zone. Static groundwater levels of 239 wells were measured from different locations of the study area in April/March 2017 (Dry Season) and in August 2017 (Wet Season). Shallow groundwater level was measured from soil surface to water level using well water depth logger (Qin and Li, 1998). The result showed that groundwater level ranged from 0.6 m to 12.5 m in dry season and 0.1 m to 13 m in wet season. The groundwater level increased by average of 34.68% (n = 235) as compared to that in dry season. Increase in the groundwater level suggests recharge of groundwater in wet season of the study area. The flow pattern of groundwater levels from the study shows flow of shallow groundwater towards the major rivers of that particular river watershed. As a consequence, seepage flow and piping erosion is likely along the riverbank slopes. Increase in recharge of groundwater during wet season exhibits that the northern region of the Kathmandu Valley is potential for groundwater recharge and can be used to manage water for the dry period.